Surgical treatment of adolescent internal condylar resorption (AICR) with articular disc repositioning and orthognathic surgery in the growing patient—a pilot study - Bodine, Trevor P.; Wolford, Larry M.; Araujo, Eustaquio; Oliver, Donald R.; Buschang, Peter H. (Progress in orthodontics, 2016)
Background The aim of this study was to better understand how surgical repositioning and stabilization of anteriorly displaced articular discs using the Mitek mini-anchor technique affects condylar growth in growing patients with adolescent internal condylar resorption (AICR). Methods Twenty-two adolescent patients diagnosed with AICR and anterior temporomandibular disc displacement were compared to untreated control subjects without AICR matched for age, sex, and Angle classification. Pre-surgical (T1 and T2) and post-surgical (T3 and T4) mandibular tracings were superimposed on natural stable structures to evaluate the horizontal, vertical, and total changes in the position of condylion. Results The treated group showed an overall decrease in condylar height pre-surgically and statistically significant changes in condylar growth direction between the pre- and post-surgical observation periods. Pre-surgically, the treated group showed significantly more posterior condylar growth than the control group; they also showed inferior condylar growth, while the controls showed superior growth. Controls and patients in the treated group showed no significant differences in condylar growth post-surgically. Conclusions Adolescent patients diagnosed with AICR and anterior disc displacement treated with mandibular ramus and maxillary osteotomies, along with Mitek anchors to reposition internally deranged discs, showed post-surgical normalization of condylar growth.